Spatial analysis of visitors to the National Institute for Oncology in the municipality of Misurata (Libya Journal of Geographical Studies, 2023)
The quality of services in general and health services in particular is an important element that contributes to the advancement and progress of countries. This study is of importance in detecting the spread of such diseases (cancerous tumors) in Libya and giving an indication for officials to pay attention to the National Institute for Oncology and provide it with diagnostic and therapeutic services to raise its level. The study aims to give a clear picture of the National Institute for Oncology in Misrata, And on the spatial dimension of the health services provided by the institute, and to identify the demographic characteristics of patients with oncological diseases in terms of age and gender. The study relied on a set of tools such as books, magazines, reports, statistics and data collected from the institute. The study also relied on the SPSS program to analyze the collected data and the arc GIS program to produce photographic maps of the subject of the study. One of the most important results of the study is that most of the visitors to the institute are from the western and central regions of the country, where the western region came in the first place with a rate of 40.18%, and the central region came in the second place with a rate of 35.21% of the total number of visitors during the study period. The highest category of attendees was the age group 60 years and over, with 49.97% of the total number of attendees being males. The highest age group was 60 years and over, with a rate of 28.33% of the total number of female visitors. Among them, breast cancer diseases in women came in the first place with a rate of 26.7% of the total diseases, in the second place colon diseases with a rate of 20.15% of the total diseases, and in the third place lung diseases with a rate of 10.17%.
Keywords: National Cancer Institute; Cancerous tumors; age groups